Mobile journalism, cellphilms, and the use of the StoryMaker Multimedia Software at a Zimbabwean media training university - Nhamo Anthony Mhiripiri; Oswelled Ureke (IGI Global, 2023)
This chapter deals with the teaching of students in the use of a smartphone application for cellphone filming and mobile journalism at the Media and Society Studies Department Midlands State University (MSU) in Zimbabwe. The smartphone and Storymaker multimedia software application used for training was provided by a Zimbabwean non-governmental organisation – Her Zimbabwe – which is affiliated to the Netherlands-based media civil society group Free Press Unlimited. MSU is a state university. Its administrative culture is intricately linked to the ZANU PF led government of President Robert Mugabe. The training offered to media students is conducted with caution. Students make cellphone films (cellphilms) and practice mobile journalism (mojo) to produce media content. The chapter critiques students' media content, especially why it appears apolitical. Self-censorship arising from socialization and interpellation is implicated in the restrained nature of students' productions, and lecturers and the civil society organisation involved are also cited as oblique gatekeepers in the production chain.